Light-Switchable Membrane Permeability in Giant Unilamellar Vesicles - Paola Albanese; Simone Cataldini; Chloe Z.-J. Ren; Nadia Valletti; Jlenia Brunetti; Jack L.-Y. Chen; Federico Rossi (MDPI AG, 2022)
In this work, giant unilamellar vesicles (GUVs) were synthesized by blending the natural phospholipid 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) with a photoswitchable amphiphile (1) that undergoes photoisomerization upon irradiation with UV-A (E to Z) and blue (Z to E) light. The mixed vesicles showed marked changes in behavior in response to UV light, including changes in morphology and the opening of pores. The fine control of membrane permeability with consequent cargo release could be attained by modulating either the UV irradiation intensity or the membrane composition. As a proof of concept, the photocontrolled release of sucrose from mixed GUVs is demonstrated using microscopy (phase contrast) and confocal studies. The permeability of the GUVs to sucrose could be increased to ~4 × 10-2 μm/s when the system was illuminated by UV light. With respect to previously reported systems (entirely composed of synthetic amphiphiles), our findings demonstrate the potential of photosensitive GUVs that are mainly composed of natural lipids to be used in medical and biomedical applications, such as targeted drug delivery and localized topical treatments.